Корни суфизмa и его рaспрострaнение в Центрaльной Азии и Ирaне (Вестник КазНУ. Серия Востоковедения, 2018)
The article deals with the concept of Sufism, as well as its elements and philosophical influence. Thesignificance of Sufism in the formation of Muslim society, as well as the expansion in Central Asia andthe stage of development of this trend are analyzed. The role of Sufi orders in the formation of answersto the challenges of the Muslim faith in the modern era is explored. It emphasizes the openness of Sufismfor external influence and its end of the Sufi order in modern times. It also mentions the widespread disseminationof mystical ideas through the poetry of Sufi literatures among Muslims, the continuation ofSufi’s responsibility for large-scale missionary activity and political activity of leaders.